Analysis of Komodo Airport Development Potential in Supporting the Tourism Sector in Labuan Bajo - Andi Nurhayati; Fryda Fatmayati (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Transportation has a very important role in economic development, because transportation services facilitate the distribution of circulation and traffic of goods and services. The performance of the national economic network cannot run without the support of transportation. As one of Indonesia's leading tourism potentials, Labuan Bajo needs infrastructure support such as an airport. To facilitate the accessibility of tourists, especially foreign tourists, the provision of an international airport can be considered. This study uses qualitative research methods, the subject of this research is Komodo Airport. Collecting data using interviews, observation, and documentation. After obtaining the data, the researcher performs data processing through the stages of data reduction, data presentation, and drawing conclusions. Based on the research results obtained by researchers, at Komodo Labuan Bajo Airport, the role of Komodo Airport in supporting the Labuan Bajo tourism sector is to provide services, and provide tourism support facilities by optimizing the information section, and the airport security section. The strategy for Komodo airport in contributing to tourism in Labuan Bajo is by promoting tourism objects in Labuan Bajo, cooperating with travel agents, adding flight schedules (Extra Flights). The obstacles faced by the airport in carrying out the airport's role in supporting the tourism sector are the lack of contribution from the Labuan Bajo regional government in supporting airport activities, the lack of a budget to support facilities and infrastructure.